Enhancing IVF Success in Challenging Infertility Cases: The Role of PRGF, GH, and Endometrial Optimization - Sudhanshu Dakre; Jarul Shrivastava; Namrata Anjankar; Deepti Shrivastava; Aakash More; Shradha M. Ulhe (Journal of Pharmacy and Bioallied Sciences)
Infertility in patients with reduced ovarian reserve and thin endometrial lining continues to pose a great challenge for successful in vitro fertilization. In the present case, a patient with a thin endometrium and low ovarian reserve resulted in a positive pregnancy with a specific IVF treatment plan. It included plasma-rich growth factors, growth hormone, supplementation along with some interventional support of endometrial scratching, and assisted hatching. Endometrial scratching and assisted hatching further optimized implantation potential. The use of these interventions hence promoted successful implantation of the embryo that contributed to positive pregnancy outcome and the birth of a healthy baby at 39 weeks. This case showed how individual ongoing comprehensive treatments definitively made a huge difference in the success of reproductive medicine.